2019
DOI: 10.1002/smll.201904105
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Yttrium Codoped Co(OH)F Nanoarray as Highly Efficient and Bifunctional Electrocatalysts for Overall Water Splitting

Abstract: this regard, highly efficient and durable electrocatalyst is imperative to enhance the energy efficiency.To date, precious metal-based catalysts, for example, RuO 2 , IrO 2 , and Pt exhibit excellent catalytic performance for water splitting. [5,6] But, the broad use of these noble metals has been severely hampered by their scarcity and expensive price. [7] Hence, it has taken a great deal of research to develop the economical alternatives. Various transition metal (hydr)oxides, [3,8,9] selenides, [10,11] sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…After the revelation in monoatomic single-layered form phosphorene, it gained significance owing to its optoelectronic properties, high charge-carrier mobility, , and ability to be exfoliated with different thicknesses ranging between 3 and 40 nm. Hence, a set of band gaps from 0.3–2.0 eV is observed depending on thickness. , BP finds its applications in several fields, such as surface electrocatalysis , and photocatalysis, for its tunable band gap. As the application of BP involves several aqueous-phase systems, it is essential to understand the interaction of water molecules with the surface of BP.…”
Section: Introductionmentioning
confidence: 99%
“…After the revelation in monoatomic single-layered form phosphorene, it gained significance owing to its optoelectronic properties, high charge-carrier mobility, , and ability to be exfoliated with different thicknesses ranging between 3 and 40 nm. Hence, a set of band gaps from 0.3–2.0 eV is observed depending on thickness. , BP finds its applications in several fields, such as surface electrocatalysis , and photocatalysis, for its tunable band gap. As the application of BP involves several aqueous-phase systems, it is essential to understand the interaction of water molecules with the surface of BP.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of a third metal element (e.g., Cr, Cu, Ni, or W) into the Fe–Co oxyhydroxide system can enhance the conductivity, thus accelerating the water oxidation procedure. It has been reported that the codoping of yttrium and phosphorus into Co­(OH)F would tune electronic environment and expedite electron transfer, thus improving OER performance . The coating of spherical Ni­(OH) 2 with Y­(OH) 3 would improve the charge acceptability of Ni­(OH) 2 at elevated temperature .…”
Section: Introductionmentioning
confidence: 99%
“…S1 show a 3D network architecture characterized by hierarchical nanosheet arrays that endows the SA-Ru/ Co(OH)F with a large specific surface area. The 3D network architecture provides more exposed active sites and favors the contact of electrode materials with electrolyte, as well as benefits the diffusion of reactants and release of produced gas in numerous 3D cavities; all these advantages greatly contribute to improving the activity and reaction kinetics of OER [29,30]. Fig.…”
Section: Resultsmentioning
confidence: 99%